Influence of LA/Ti molar ratio on the complex synthesis of anatase/brookite nanoparticles and their hydrogen production. (16th February 2021) - Cihlar, Jaroslav; Tinoco Navarro, Lizeth Katherine; Kasparek, Vít; Michalicka, Jan; Cihlar, Jaroslav; Kastyl, Jaroslav; Castkova, Klara; Celko, Ladislav
Abstract: Heterophase TiO2 nanoparticles formed in the presence of a very low concentration of a substance with two donor groups were studied and the mechanism of their formation was proposed. The TiO2 nanoparticles were prepared by low-temperature hydrolysis and polycondensation of Ti (IV) n-propoxide in the presence of lactic acid (LA). The phase composition of the nanoparticles was controlled by the LA/Ti molar ratio ranging from 0.02 to 3.0. At low LA/Ti molar ratios, biphasic anatase-brookite was formed, at average LA/Ti molar ratios, anatase-brookite-rutile particles were formed, and at high molar ratios, pure anatase was formed. By using the low LA/Ti molar ratios, the low-temperature colloidal synthesis made it possible to control the composition of heterophase mesoporous TiO2 nanoparticles with a high specific surface area and high photocatalytic activity in the production of hydrogen by water splitting. The highest photocatalytic activity was exhibited by anatase-brookite nanoparticles containing 46–65% brookite, synthesized at LA/Ti molar ratios in the range of 0. 033 to 0.1. Graphical abstract: Image 1 Highlights: Sol-gel complex synthesis of biphase anatase-brookite (A-B)nanoparticles Mode of Ti-ligand bonds facilitates the formation of heterophase junctions Heterophase titania nanoparticles for hydrogen production Cooperative photocatalytic behaviour of the anatase and brookite phases.